Comparing Parents of Children With Down Syndrome at Different Life Span Stages. Issue 4 (8th June 2016) - Nelson Goff, Briana S.; Monk, J. Kale; Malone, Juliana; Staats, Natira; Tanner, Allison; Springer, Nicole P.
Abstract : The present study explored the experiences of parents of children with Down syndrome at different phases of the life span. Using a mixed‐method design, the current study included 445 participants who were divided into 4 groups based on the age of the child: (a) parents of children under 5 years of age (early childhood), (b) parents of children between 5 and 11 years of age (middle childhood), (c) parents of children between 12 and 18 years of age (adolescence), and (d) parents of children over the age of 18 (chronological adults). Parents reported higher coping strategy scores during the middle childhood and adolescent years than early childhood or later years (adult children). Qualitative data identified key areas that parents across the 4 groups reported, including acceptance of the diagnosis, having a positive attitude, their child's developmental level, and other internal and external factors that contribute to their attitudes and coping.